CARICOM agriculture and the FTAA : priorities and interest - Taylor, Timothy G. (Caribbean RNM/IDB Project Christ ChurchBB, 2001)
Examines CARICOM agriculture within the context of the FTAA and against the backdrop of the commonalities and differences that make this regional grouping unique.